2022
DOI: 10.1158/1055-9965.epi-21-1023
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolomics and Breast Cancer Risk over 20 Years of Follow-up among Postmenopausal Women in the Nurses' Health Study

Abstract: Background: Metabolite profiles provide insight into biologic mechanisms contributing to breast cancer development. We explored the association between prediagnostic plasma metabolites (N = 307) and invasive breast cancer among postmenopausal women in a nested case–control study within the Nurses' Health Study (N = 1,531 matched pairs). Methods: Plasma metabolites were profiled via LC/MS-MS using samples taken ≥10 years (dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…This general observation was coherent with the results of previously published reports. Brantley and coworkers reported that poly-unsaturated triglycerides and cholesteryl esters were inversely associated with breast cancer in the American Nurses’ Health Study ( 12 ). His and coworkers, using an earlier version of the analytical platform applied in the current study, showed the inverse correlation of several phosphatidylcholines and sphingomyelins with breast cancer risk in the European Prospective Investigation into Cancer (EPIC) cohort ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This general observation was coherent with the results of previously published reports. Brantley and coworkers reported that poly-unsaturated triglycerides and cholesteryl esters were inversely associated with breast cancer in the American Nurses’ Health Study ( 12 ). His and coworkers, using an earlier version of the analytical platform applied in the current study, showed the inverse correlation of several phosphatidylcholines and sphingomyelins with breast cancer risk in the European Prospective Investigation into Cancer (EPIC) cohort ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…A few nested case-control studies compared pre-diagnostic samples collected from women who were cancer-free at the baseline, then developed breast cancer during a few years of follow-up, and matched women who remained healthy. These studies indicate that an increased risk of breast cancer was associated with an increased level of certain amino acids ( 10 12 ) or sex steroid metabolites (especially for postmenopausal women) ( 13 , 14 ). On the other hand, an inverse association between the risk of BC and serum/plasma level of phosphatidylcholines ( 15 ), lysophosphatidylcholines ( 11 , 16 ), cholesterol esters ( 12 ), and other lipid compounds ( 10 , 12 , 14 ) was observed.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Brantley et al. has used liquid chromatography tandem mass spectrometry (LC-MS/MS) for the identification of 307 metabolites including phenylalanine, tyrosine and tryptophan in plasma, wherein the correlation of amino acid regulation with breast cancer development including TNBC was demonstrated [ 11 ]. The LC-MS/MS based on triple quadrupole mass spectrometer is considered as the gold standard for amino acids quantification, which however needs time-consuming sample pretreatment, complicated operations, long analysis time per sample and is at high cost, limiting its wide application in clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…As abnormalities in gene and protein levels would eventually be reflected in metabolism, metabolomics analysis was proposed (Huang et al, 2018). In fact, differential metabolomics analysis was found to be effective in the studies of various kinds of diseases and disorders including obesity, depressive disorder (Du et al, 2021), and cancerous disease (Brantley et al, 2022), indicating the variety of effects of noise exposure. In a recent study, plasma metabolomics analysis was performed on noiseexposed workers in a factory, and 20 metabolites were identified to be potential markers associated with NIHL (Miao et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%